Strong Association of Combined Genetic Deficiencies in the Classical Complement Pathway With Risk of Systemic Lupus Erythematosus and Primary Sjögren's Syndrome. Issue 11 (7th October 2022) - Lundtoft, Christian; Sjöwall, Christopher; Rantapää‐Dahlqvist, Solbritt; Bengtsson, Anders A.; Jönsen, Andreas; Pucholt, Pascal; Wu, Yee Ling; Lundström, Emeli; Eloranta, Maija‐Leena; Gunnarsson, Iva; Baecklund, Eva; Jonsson, Roland; et al.
Abstract : Objective: Complete genetic deficiency of the complement component C2 is a strong risk factor for monogenic systemic lupus erythematosus (SLE), but whether heterozygous C2 deficiency adds to the risk of SLE or primary Sjögren's syndrome (SS) has not been studied systematically. This study was undertaken to investigate potential associations of heterozygous C2 deficiency and C4 copy number variation with clinical manifestations in patients with SLE and patients with primary SS. Methods: The presence of the common 28‐bp C2 deletion rs9332736 and C4 copy number variation was examined in Scandinavian patients who had received a diagnosis of SLE (n = 958) or primary SS (n = 911) and in 2, 262 healthy controls through the use of DNA sequencing. The concentration of complement proteins in plasma and classical complement function were analyzed in a subgroup of SLE patients. Results: Heterozygous C2 deficiency— when present in combination with a low C4A copy number— substantially increased the risk of SLE (odds ratio [OR] 10.2 [95% confidence interval (95% CI) 3.5–37.0]) and the risk of primary SS (OR 13.0 [95% CI 4.5–48.4]) when compared to individuals with 2 C4A copies and normal C2 . For patients heterozygous for rs9332736 with 1 C4A copy, the median age at diagnosis was 7 years earlier in patients with SLE and 12 years earlier in patients with primary SS when compared to patients with normal C2 . Reduced C2 levels in plasma ( P  = 2 × 10 −9 ) and impaired function of the classical complement pathway ( P  = 0.03) were detected in SLE patients with heterozygous C2 deficiency. Finally, in a primary SS patient homozygous for C2 deficiency, we observed low levels of anti–Scl‐70, which suggests a risk of developing systemic sclerosis or potential overlap between primary SS and other systemic autoimmune diseases. Conclusion: We demonstrate that a genetic pattern involving partial deficiencies of C2 and C4A in the classical complement pathway is a strong risk factor for SLE and for primary SS. Our results emphasize the central role of the complement system in the pathogenesis of both SLE and primary SS.